Sarah Hall geography copybook - Hall, Sarah, active 1813.
Geography copybook (32 pages) kept by Hall containing descriptions of southern states and territories including Georgia, Kentucky, Louisiana, Maryland, Mississippi, North Carolina, South Carolina, Tennessee, and Virginia; "Spanish Dominions" (Florida); and "Unknown Regions" (Mexico). Some descriptions are accompanied by colored drawings of flowers. Includes descriptions and drawings of the Ptolemaic, Tychonic, and Copernican systems of the universe; a drawing of the earth showing the equator, the poles, and the frigid, torrid, and temperate zones; and a sketch of a boating scene. A later penciled note on the inside cover states erroneously that Hall was the mother of Supreme Court Chief Justice Salmon P. Chase.
Student at Elizabeth Seton's school, Cornish, N.H., June-July 1813.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Astronomy; Boats and boating -- Pictorial works; Flowers -- Pictorial works; Geography; Earth (Planet) -- Pictorial works; Florida -- Description and travel; Georgia -- Description and travel; Kentucky -- Description and travel; Louisiana -- Description and travel; Maryland -- Description and travel; Mexico -- Description and travel; Mississippi -- Description and travel; North Carolina -- Description and travel; South Carolina -- Description and travel; Southern States -- Description and travel; Tennessee -- Description and travel; Universe -- Pictorial works; Universe -- Description and travel; Virginia -- Description and travel; Students